Development of Pricing Models in the Sugar Market and Their Forecasting on Commodity Exchanges (Economics and region, 2020)
The article considers the dynamics of prices for futures contracts in the sugar market, in particular-two («Sugar No. 11 Futures», «Sugar No. 16 Futures») on the Intercontinental Commodity Exchange – ICE; one («White Sugar Futures (No. 407)») on the London International Financial Futures and Options Exchange – Liffe (LIFFE); one («Sugar White») on the Zhengzhou Commodity Exchange – ZCE. In this article, in order to forecast the price of sugar on London intercontinental financial futures and options exchange – Liffe. Correlation and regression analysis is applied and the main stages of building a multiple linear correlation and regression model are presented. The dynamics of the average annual value of the White Sugar Futures contract (No. 407) is given. The Fisher F-test was used for rapid diagnostics of the adequacy of the multiple correlation-regression model.
Keywords: commodity exchanges; pricing; sugar market; forecasting